Survei Penerapan Sport Massage Pada Atlet Olahraga Permainan Bola Besar Sebelum dan Pasca Pertandingan - Irfani Sandra; Rias Gesang Kinanti; Ahmad Abdullah (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2023)
Sport massage is a massage treatment that treats the physical, physiological, and psychological aspects of athletes, sport massage has so many benefits, including improving blood circulation, helping relieve muscle injuries, recuding stress, increasing body flexibility, and reducing anxienty . It can be used before or after exercise. If used before sporting activities will greatly assist in the lengthening and loosening of soft tissues. Sport Massage should also be a concern for all sports actors except athletes, the purpose of this research is to find out the application of sport massage to big ball game athletes in Malang. This research method uses descriptive quantitative using a survey approach. The number of respondents in this study were 5 coaches from big ball game athletes. The results of the study using the IBM SPSS 26.0 analysis technique obtained a mean value of 93 and a standard deviation of 15.4. This means that the application of sports massage before and after the match is carried out more often before the game than after the match with a value of 94%. The results of the research can be concluded that the implementation of the Big Ball Game Athletes in Malang is still not balanced, so it needs to be improved again.